Formulation and Characterization of Cinnamon Bark Essential Oil (Cinnamomum burmanii) Nanoemulsion as Poultry Feed Additive Candidate - Baskara, Aji Praba; Ariyadi, Bambang; Dono, Nanung Danar; Martien, Ronny; Zuprizal, Zuprizal (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study was conducted to formulate and to characterize nanoemulsion of cinnamon (Cinnamomum burmanii) bark essential oil (CBO). The compositions of cinnamon essential oil were qualitatively analyzed using Gas Chromatography-Mass Spectrophotometry (GC-MS). The formulations which consisted of CBO, virgin coconut oil (VCO), surfactant (Tween 80), and co-surfactant (PEG 400) were investigated to prepare emulsification method. The Transmittance value was carried out to choose the best nanoemulsion formulation. Droplet size, polydispersity index (PI), zeta potenzial, and morphology were studied to chacterize the nanoemulsion formulation. Based on the transmittance value after dispersion into aqueous phase, formulation consisting of CBO, VCO, Tween 80, PEG 400 (0.75; 0.25; 4; 1 v/v) was chose. The formulation of nanoemulsion having mean droplet diameters of 20.2 mm with polydispersity index (PI) 0.463 and potensial zeta -0.8 mV. The nanoemulsion morphology using transmission electron microscopy (TEM) imaging was demonstrated the oil droplets in nano-scale. This study showed that nanowmulsion of cinnamon bark essential oil could be applied as poultry feed additive.